Development and validation of quantification method for fluconazole in human serum using ultra-high-performance liquid chromatography-tandem mass spectrometry - Mohd Salleh Rofiee (Tanjong Malim, 2022)
Development and validation of quantification method for fluconazole in human serum using ultra-high-performance liquid chromatography-tandem mass spectrometry by Mohd Salleh Rofiee